The resistance status of Aedes aegypti larvae to Temephos in Depok, Sleman, Yogyakarta - Yuniyanti, Mia Munawaroh; Umniyati, Sitti Rahmah; Ernaningsih (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2021)
There are still many cases of dengue hemorrhagic fever and tend to increaseover time. One strategy to reduce the increase in cases of dengue infection isto eradicate Aedes aegypti as a vector using insecticides. The use of insecticidesfor a long time can cause resistance. The purpose of this study was to determinethe resistance status of Aedes aegypti larvae against temephos in Depok, Sleman.This quasi experimental test was carried out on 3rd instar larvae of aedesaegypti from RW 9 and 10 Minomartani, Depok, Sleman. The treatment groupwas exposed 0.02 ppm temephos for 24 hours. The analysis was presented in theform of percentage of larval mortality and resistance categories based on WHOguidelines. The mortality percentage of Aedes aegypti larvae in RW 9 was 100%,while the mortality from RW 10 was 97%. Aedes aegypti larvae in Depok district,Sleman are still susceptible to temephos at a dose of 0.02 ppm.